Precancer Lesions of the Cervix among Treatment Experienced HIV Positive Women at University College Hospital, Ibadan, Nigeria (2021)
Background: Cervical precancer lesions, caused by persistence of human papilloma virus (HPV) infection, is common among women living with Human immunodeficiency virus (HIV) infection. However, there remains paucity of information on these dysplastic lesions especially in low- and middle-income countries of the world as there are few programmes that have incorporated routine screening as a standard of care. Aim: To determine the pattern of precancer lesions of the cervix among treatment experienced HIV positive women in a large antiretroviral therapy programme in South West Nigeria. Study Design: Retrospective review of clinical records. Place and Duration of Study: HIV Programme in College of Medicine, University of Ibadan/University College Hospital, Ibadan, Nigeria between January 2014 and December 2015. Methodology: A review of the Pap smear results of 468 women attending the antiretroviral therapy (ART) clinic at the University College Hospital (UCH) Ibadan over a 2-year period was done. The cytological results were analyzed with biosocial variables. Level of significance was set at 95% confidence level. Results: The mean age of the participants reviewed was 37.1+/- 8.7 years. The mean duration of ART among the participants was 19.5 (±14.0) months. The prevalence of any form of squamous Intraepithelial lesions (SIL) varied from 10.0% among those on ART for up to 12 months to 1.4% among those with more than 18 months of ART use (p=022) and polygamous relationship is significantly associated with dysplastic cervical lesions among this studied cohort (p=0.043) Conclusion: While ART appears to have anti-Human Papillomavirus (HPV) activities as observed in the pattern of cervical dysplastic lesions, polygamy, a common family setting in this environment seems to promote development of SIL among these WLHIV. These findings require further studies to corroborate in the light of limitations of difficulty in disaggregating the duration of HIV diagnosis from the onset of treatment as most were already on treatment before the screening and failure of baseline Pap smear test at the entry point to determine the rate of progression.